Arterial and venous thromboembolism risk associated with blood eosinophils: A systematic review and meta‐analysis. Issue 5 (7th October 2022) - Xu, Wei‐Jie; Wang, Shang; Yuan, Ping; Wang, Lan; Huang, Jun‐Xia; Jiang, Rong
Abstract: The association between blood eosinophil (EOS) counts and arterial/venous thrombosis is unclear. We aim to explore whether EOS count is a risk factor for thrombosis. We searched several databases and preprint platforms using core terms 'eosinophil', 'myocardial infarction', 'ischemic stroke', and 'venous thromboembolism' (VTE), among others. Studies comparing the odds ratios (ORs) or risk ratios (RRs) of EOSs with the abovementioned diseases were eligible. Overall, 22 studies were included. A high EOS count was associated with acute coronary artery thrombosis events (OR: 1.23, 95% CI: 1.15–1.32), short‐term cerebral infarction and mortality (RR: 2.87, 95% CI: 1.49–5.51). The short‐term risk of VTE was more common in patients with EOS‐related diseases (RR: 6.52, 95% CI: 2.42–17.54). For coronary artery disease, a high EOS count was a protective factor against 6‐month to 1‐year mortality (RR: 0.56, 95% CI: 0.45–0.69) but was associated with long‐term mortality (RR: 1.64, 95% CI: 1.25–2.14). Therefore, we conclude that for coronary artery thrombosis, EOS count is not associated with AMI events in general population. It may be associated with NSTEMI and STEMI in CAD patients, but more studies are needed to confirm this. In addition, EOS count is associated with an increased risk of both short‐ and long‐term mortality but is not predictive of the composite endpoints. For cerebral artery thrombosis, EOS count may be associated with cerebral infarction and could lead to an increased risk of poor short‐term prognosis. For VTEs, EOS count was a risk factor for some patients, especially those with acute‐phase EOS‐related diseases. Abstract : We searched 22 related articles from the PubMed, Embase, Cochrane Library databases and preprint platforms. Then we conducted a systematic review and meta‐analysis to assess the association between blood EOS count and thrombotic events and their associated adverse outcomes in patients with various arterial or venous thrombosis disorders.